MeCP2_e2 partially compensates for lack of MeCP2_e1: A male case of Rett syndrome - Ryo Takeguchi (Molecular Genetics & Genomic Medicine, 2020)
Abstract Background Rett syndrome (RTT) is a neurodevelopmental disorder that predominantly affects girls. Its causative gene is the X‐linked MECP2 encoding the methyl‐CpG‐binding protein 2 (MeCP2). The gene comprises four exons and generates two isoforms, namely MECP2_e1 and MECP2_e2. However, it remains unclear whether both MeCP2 isoforms have similar function in the brain. Methods We report a case of a boy with typical RTT. Male cases with MECP2 variants have been considered inviable, but somatic mosaicism of the variants can cause RTT in males. Whole‐exome sequencing was performed to search for the genetic background. Results A novel nonsense and mosaic variant was identified in exon 1 of MECP2, and the variant allele fraction (VAF) was 28%. Our patient had the same level of VAF as that in reported male cases with mosaic variants in MECP2 exon 3 or 4, but manifested RTT symptoms that were milder in severity compared to those in these patients. Conclusion This is probably because the variants in MECP2 exon 3 or 4 disrupt both isoforms of MeCP2, whereas the variant in exon 1, as presented in this study, disrupts only MeCP2_e1 but not MeCP2_e2. Therefore, our findings indicate that MeCP2_e2 may partially compensate for a deficiency in MeCP2_e1.